Pengaruh Perceived Price dan Product Quality Terhadap Repurchase Intention Melalui Customer Satisfaction pada Game Mobile Legends: Bang Bang - Naufal Dwiranzah; Munawaroh Munawaroh; Ryna Parlyna (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research is motivated by the phenomenon of declining annual revenue for the game Mobile Legends: Bang Bang (MLBB) in 2025, which indicates an issue in players' repurchase intention due to complaints regarding price fairness (perceived price) and product quality. This study aims to analyze the effect of perceived price and product quality on repurchase intention with customer satisfaction as a mediating variable among MLBB players. The research method employed is quantitative, utilizing an online questionnaire distributed to 142 respondents consisting of Universitas Negeri Jakarta students in Jabodetabek who met the sampling criteria. The data analysis technique applies Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results indicate that perceived price and product quality have a positive and significant effect on customer satisfaction and repurchase intention. Moreover, customer satisfaction is proven to serve as a significant mediator bridging the effects of perceived price and product quality on repurchase intention. These findings emphasize that sustaining players' repurchase intention in the long term heavily relies on the developer's capability to foster customer satisfaction through fair pricing strategies and innovative, high-quality product designs.